2021
DOI: 10.1038/s41598-021-97614-8
|View full text |Cite
|
Sign up to set email alerts
|

Seedbank persistence and emergence pattern of Argemone mexicana, Rapistrum rugosum and Sonchus oleraceus in the eastern grain region of Australia

Abstract: A thorough understanding of the emergence pattern and persistence of weed seeds is a prerequisite in framing appropriate weed management options for noxious weeds. In a study conducted at the University of Queensland, Australia, the emergence and seed persistence behavior of three major weeds Sonchus oleraceous, Rapistrum rugosum, and Argemone mexicana were explored with seeds collected from Gatton and St George, Queensland, Australia, with an average annual rainfall of 760 and 470 mm, respectively. Seed persi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The seeds of A. mexicana could persist in the soil for a longer period if fresh seed production, reinfestation, and dispersal are not controlled. In Australia, it was observed that at 2 and 10-cm soil depths, >30% of seeds of A. mexicana were viable after 42 months of seed burial (Manalil and Chauhan 2021). In another study, it was observed that plants of A. mexicana were unable to produce seeds when infested in wheat crop due to high competition offered by the crop (Manalil and Chauhan 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The seeds of A. mexicana could persist in the soil for a longer period if fresh seed production, reinfestation, and dispersal are not controlled. In Australia, it was observed that at 2 and 10-cm soil depths, >30% of seeds of A. mexicana were viable after 42 months of seed burial (Manalil and Chauhan 2021). In another study, it was observed that plants of A. mexicana were unable to produce seeds when infested in wheat crop due to high competition offered by the crop (Manalil and Chauhan 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Most weed species are known to be hardy and persistent in nature, producing thousands of seeds that can withstand various adverse environmental conditions, while staying dormant in the soil for long periods ( Manalil and Chauhan, 2021 ; Chauhan and Manalil, 2022 ). When optimal germination conditions are met, the seeds will germinate and compete with the crops sown on the same area of land.…”
Section: Challenges In Weed Managementmentioning
confidence: 99%
“…The germination of R. rugosum was found to be >85% at temperatures ranging from 15/5 to 25/15 C (day/night temperature), suggesting the ability of this weed to germinate in winter environments (Manalil et al 2018). With optimal germination temperatures coinciding with chickpea cultivation, long seed persistence (>3.5 yr) in the soil and the ability to emerge from near the soil surface may increase R. rugosum infestation in chickpea crops in Australia (Gill et al 2022; Manalil and Chauhan 2021).…”
Section: Introductionmentioning
confidence: 99%